Demand-driven Acquisition of Print Books: Applying 21st-Century Procurement Strategies to a 5th-Century Format. Issue 2 (3rd July 2019) - England, Mark M.; Anderson, Rick
Abstract: The Marriott Library at the University of Utah was an early champion of the demand-driven model of acquiring ebooks. Beginning in 2017, the Marriott Library applied a similar approach to the acquisition of print books. Demand-driven acquisition of physical formats is a means for stretching compressed library budgets and a technique for managing the explosion in book publishing. Demand-driven acquisition addresses publishers that refuse to sell individual electronic books to libraries and better serves disciplines like the fine arts. The Marriott Library's experiences with demand-driven print acquisition are discussed and compared with other libraries that are testing this acquisition method.